2018
DOI: 10.1016/j.disc.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Query complexity of mastermind variants

Abstract: We study variants of Mastermind, a popular board game in which the objective is sequence reconstruction. In this two-player game, the so-called codemaker constructs a hidden sequence H = (h 1 , h 2 , . . . , h n ) of colors selected from an alphabet A = {1, 2, . . . , k} (i.e., h i ∈ A for all i ∈ {1, 2, . . . , n}). The game then proceeds in turns, each of which consists of two parts: in turn t, the second player (the codebreaker ) first submits a query sequence Q t = (q 1 , q 2 , . . . , q n ) with q i ∈ A f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…El Ouali et al [5] combined the upper bound with a lower bound of n queries, which is implied by a codemaker (cheating) strategy. It improved the lower bound of n − log log n by Berger et al [2]. However, a gap between Ω(n) and O(n log 2 n) remains for this Mastermind variant.…”
Section: Introductionmentioning
confidence: 84%
“…El Ouali et al [5] combined the upper bound with a lower bound of n queries, which is implied by a codemaker (cheating) strategy. It improved the lower bound of n − log log n by Berger et al [2]. However, a gap between Ω(n) and O(n log 2 n) remains for this Mastermind variant.…”
Section: Introductionmentioning
confidence: 84%
“…From this perspective, Jiang and Polyanskii [JP19] recently showed that the minimum number of queries is (2 + o(1))n log k log n ) for any constant k. For k ≤ n, the non-adaptive complexity of black-white-peg Mastermind is the same as black-peg Mastermind, since the non-adaptive strategy using only black-peg queries has reached the entropy lower bound. Contrarily, for k > n it is still not clear whether the non-adaptive strategy with black-white-peg queries can reduce currently the best bound O(k log k) achieved by the one with only black-peg queries [DDST16,BCS18].…”
Section: Related Workmentioning
confidence: 99%
“…The original version was completely characterized by [Knu77], who showed upper and lower bounds of 5 queries for deterministic strategies. The n-position k-color generalization of the game was studied in [Chv83], which sparked a line of research that lead to progressive improvement in upper and lower bounds for this problem, both in the original version of the game as well as in related variants of the game [BCS18]. As these variants are not the focus of this work, we refer the reader to the expositions of [DDST16,BCS18] for more details on this literature.…”
Section: Introductionmentioning
confidence: 99%